Using unified modelling language to model the publish/subscribe paradigm in the context of timed Web services with distributed resources. Issue 6 (2nd November 2017) - Valero, Valentín; Cambronero, María-Emilia
ABSTRACT: In this paper, we present a unified modelling language (UML) framework to model timed Web services with distributed resources. We provide a graphical model of timed Web services that integrates the publish/subscribe paradigm in the context of distributed resources, with the goal that users have a formal framework to design this kind of systems. A formalization is then provided by using UML sequence diagrams with Combined Fragments (CFs) to represent the interactions between the roles involved and Web Services Resource Framework as a standard for the management of distributed resources. The formalization is based on a two-level process algebra. At the top level we have the CF description, and at the bottom the interactions inside them. An operational semantics is then defined for this model, and two case studies are presented to illustrate the applicability of this formalism.